Joint UK societies' 2019 consensus statement on renal denervation. Issue 19 (10th July 2019) - Lobo, Melvin D; Sharp, Andrew S P; Kapil, Vikas; Davies, Justin; de Belder, Mark A; Cleveland, Trevor; Bent, Clare; Chapman, Neil; Dasgupta, Indranil; Levy, Terry; Mathur, Anthony; Matson, Matthew; et al.
Abstract : Improved and durable control of hypertension is a global priority for healthcare providers and policymakers. There are several lifestyle measures that are proven to result in improved blood pressure (BP) control. Moreover, there is incontrovertible evidence from large scale randomised controlled trials (RCTs) that antihypertensive drugs lower BP safely and effectively in the long-term resulting in substantial reduction in cardiovascular morbidity and mortality. Importantly, however, evidence is accumulating to suggest that patients neither sustain long-term healthy behaviours nor adhere to lifelong drug treatment regimens and thus alternative measures to control hypertension warrant further investigation. Endovascular renal denervation (RDN) appears to hold some promise as a non-pharmacological approach to lowering BP and achieves renal sympathectomy using either radiofrequency energy or ultrasound-based approaches. This treatment modality has been evaluated in clinical trials in humans since 2009 but initial studies were compromised by being non-randomised, without sham control and small in size. Subsequently, clinical trial design and rigour of execution has been greatly improved resulting in recent sham-controlled RCTs that demonstrate short-term reduction in ambulatory BP without any significant safety concerns in both medication-naïve and medication-treated hypertensive patients. Despite this, the joint UK societies still feel that further evaluation of this therapy is warranted and that RDN should not be offered to patients outside of the context of clinical trials. This document reviews the updated evidence since our last consensus statement from 2014 and provides a research agenda for future clinical studies.